2012
DOI: 10.1209/0295-5075/99/36001
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-defect–induced diminution of thermal conductivity in silicene

Abstract: Using equilibrium molecular dynamic simulations, we calculate the phonon thermal conductivity of a graphene-like silicon nanosheet called silicene at room temperature. We find that the in-plane thermal conductivity of silicene sheets is about one order of magnitude lower than that of bulk silicon. We further investigate the effects of vacancy defects on thermal conductivity and observe its significant diminution owing to the effect of phonon-defect scattering. Our results show that phonon transport in a silice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 37 publications
9
64
1
Order By: Relevance
“…61,62 In particular, the in-plane thermal conductivity of silicene is found to be about an order of magnitude lower than for bulk Si. Vacancy defects lead to further reduction due to phonon-defect scattering.…”
Section: F Other Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…61,62 In particular, the in-plane thermal conductivity of silicene is found to be about an order of magnitude lower than for bulk Si. Vacancy defects lead to further reduction due to phonon-defect scattering.…”
Section: F Other Propertiesmentioning
confidence: 94%
“…61 It is found that short ASiNR FETs have large current on/off ratios of over 10 6 , and the output characteristic exhibits a saturation current, an effect absent for graphene nanoribbons.…”
Section: 69mentioning
confidence: 95%
“…Understanding their effect on the mechanical, electronic and structural characteristics plays an important role in nanoscale device applications. Such defects affect significantly the magnetic and electronic [17][18][19][20] as well as thermal properties of silicene [21,22]. In mechanical aspects, most of previous density-functional theory (DFT) calculations [23][24][25][26][27] and molecular dynamics (MD) simulations [27][28][29][30] have focused on the mechanical issues of pristine silicene under uniaxial tension.…”
Section: Introductionmentioning
confidence: 99%
“…Silicene a monolayer of silicon, also possessing a 2D honeycomb lattice has attracted recent attention [1][2][3][4][5][6][7]. It has an added advantage of being compatible with existing silicon electronics infrastructure [2].…”
Section: Introductionmentioning
confidence: 99%
“…Silicene is energetically favorable as a low buckled structure, the buckling distance varying from 0.02 nm to 0.046 nm. There are some reports of thermal conductivity of silicene [3][4][5][6][7]. Optimizing the Stillinger-Weber interatomic potential parameters to take into account the low buckling structure and phonon dispersion of silicene, Zhang et al [4] have calculated the LTC of silicene by equilibrium molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%